Establishment of wetland conservation networks in response to climate change and anthropogenic activities: A case study from the Liaohe River Basin in Liaoning Province, China - Kexin Chen; Shuxiu Liang; Pifu Cong; Zhaochen Sun (Ecological Indicators)
Wetlands are undergoing rapid transformations due to climate change and human activities, necessitating proactive conservation efforts. This study combined the species conservation planning model and ecological network model to create a future-oriented wetland conservation network for the Liaohe River Basin in Liaoning Province, China. The approach incorporated multi-dimensional factors, including climate change and anthropogenic activities (multi-process) as well as structural and functional aspects of wetlands (multi-level), to anticipate future challenges. The findings revealed that at the national scale, the overall trend of suitable habitats for coastal vegetation are projected to decline significantly between 2030 and 2090 under the influence of climate change. Furthermore, based on the succession patterns observed between 2010 and 2020, the wetland area is predicted to diminish from 1,575.82 km2 in 2030 to 1,015.63 km2 in 2090, while the building land area is expected to expand from 8,324.14 km2 in 2030 to 12,719.31 km2 in 2090. Human activities were identified as having a more pronounced impact on wetland conservation areas compared to climate change alone. The wetland conservation network under the SSP5-RCP8.5 climate scenario was found to be more complex, with more conservation areas compared to the SSP1-RCP2.6 climate scenario. Overall, wetlands are anticipated to follow a trajectory of degradation. This underscores the urgency of implementing conservation measures to mitigate further wetland loss. The methodology proposed for constructing a future wetland conservation network and the identified key ecological sources and ecological corridors can provide opinions and suggestions for wetland resource conservation and rationalised utilization.